(untitled) (International Journal of Food and Nutritional Sciences, 2022)
A Radio Heronian Mean Dd-distance Labeling of a connected graph G is an injective map f from the vertex set V(G) to the N such that for two distinct vertices u and v of G, DDd(u,v)+⌈(f(u)+√(f(u)f(v))+f(v))/3⌉≥1+diamDd(G) where DDd(u,v) denotes the Dd-distance between u and v and diamDd(G) denotes the Dd-diameter of G. The radio heronian Dd-distance number of f, rhmnDd(f) is the maximum label assigned to any vertex of G. The radio heronian Dd-distance number of G, rhmnDd(G) is the minimum value of rhmnDd(f) taken over all radio heronian Dd-distance labeling f of G. We study on in this paper about on radio heronian mean Dd-distance of some operation graphs.